Penanaman Nilai-nilai Karakter pada Anak melalui Pembuatan Media Kamishibai dan Metode Mendongeng Cerita Rakyat Indonesia-Jepang - Rakhman, Rizki Taufik; Suryani, Leny; Pahala, Agam Akbar; Sugianti, Desy; Lestari, Siti Khodijah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to instill character values in children through the introduction of cross-cultural folktales, the creation of kamishibai as a narrative medium, and storytelling practice. The study uses a qualitative method with a participatory approach at RPTRA Kebon Sirih, Jakarta, involving 10 children aged 6-12 years as participants. Data were collected through observation and interviews, then analyzed using the Miles and Huberman interactive analysis model. The study consists of three main phases: (1) Introduction to folktales, which showed an average post-test score of 95, indicating that participants were able to recognize and distinguish cultural elements in Nusantara and Japanese folktales, (2) Creation of kamishibai, with an average post-test score of 92, showing that participants mastered the technique of storytelling visualization using kamishibai media, and (3) Storytelling method, with an average post-test score of 90, indicating that participants were able to tell stories using the kamishibai media they created themselves. The study concludes that using kamishibai is effective in introducing cross-cultural folktales and shaping children's character through experiential learning.